PENGARUH KARAKTERISTIK SISTEM AKUNTANSI MANAJEMEN DAN DESENTRALISASI SEBAGAI VARIABEL MODERATING TERHADAP KINERJA MANAJERIAL (STUDI EMPIRIS PERUSAHAAN MANUFAKTUR DI KABUPATEN SEMARANG) - Achmad Solechan; Ira Setiawati (Fokus Ekonomi : Jurnal Ilmiah Ekonomi, 2009)
This research is aimed for investigating the influence of Characteristic of Management Accounting System (MAS) and Decentralization on Managerial Performance at Manufacturing Company in Kabupaten Semarang. Data was gathered from 68 respondents that were chosen using purposive sampling. This research employed regression technique to analyze the obtained data. This research showed that Characteristic of Management Accounting System(MAS) positively influence on Managerial Performance; Decentralization is not influence on Managerial Performance; and then the relationship between Characteristic of Management Accounting System (MAS) and Decentralization is not influence on Managerial Performance.Number Coefficient Determination (Adjusted R Square) equal to 0,812. Matter this means that Characteristic of MAS variable (X1) and Variable Characteristic MAS and Decentralization as Variable Moderating (X1.X2) to Managerial Performance (Y) have contributed to 81,20% in explaining Managerial Performance (Y). While other factors which have an effect on toManagerial Performance have its contribution equal to 18,80%.